OPTIMIZING VILLAGE ADMINISTRATION SERVICES USING THE SERVQUAL METHOD IN KLAMONO SORONG REGENCY - Wahyudien, Mohammad Arief Nur; Setyawan, Muhammad Rizky; Ahistasari, Asih; Kayatun, Siti Nur; Herdianzah, Yan (Center for Study and Journal Management FTI UMI, 2024)
Village administration services are one of the critical public services in meeting the needs of society in Indonesia. However, these services often do not meet people's expectations and needs. Various factors, including low quality of service, complicated administrative processes, and lack of use of information technology in managerial procedures cause this. This research aims to optimize the village service system, focusing on improving the quality of services in rural communities. Service Administration often experiences obstacles in providing effective and efficient public services, mainly due to inadequate resources and infrastructure. This results in rural communities being less satisfied and often experiencing difficulties accessing the public services they need. The results of this research using the Servqual method using five dimensions of service and five instrument criteria influence the village administration services of Klamono District. Of the 14 instruments used, namely communication skills, skills and abilities, services provided and information system technology used by village officials in giving service. To optimize and streamline the benefits expected by the community, a website was created to facilitate the Klamono District village administration service system.